Management of Obstetric Practice with Objective Structure Clinical Examination (Osce) Method In Laboratory Practice (Case Study At Polytechnicbhakti Asih Purwakarta) - Rati Lova, Nova; Yulianti, Lia; Humairoh, Dita; Armiyanti, Armiyanti; Yolanda Sari, Daris (Sean Institute, 2022)
The management of midwifery practice using the objective structure clinical examination (OSCE) in method of laboratory practice requires instruments that have been tested or validated so that they can provide valid assessment results, compared with instruments by the person in charge of the laboratory or a quality person who is only limited to do observations during learning. The value standard is carried out by implementing 6 value standards,. namely the theological value of students always praying before doing osce exams, ethical-legal values of students respecting lecturers and being responsible for all actions while in the laboratory, aesthetic values where students always maintain a neat osce room, quiet and beautiful room, logical-rational value: students take practical exams in accordance with existing standards, physical-physiological values students must be able to analyze each existing case, such as the diagnosis and actions to be carried out in the osce process, teleologic scores: students can use every component in the laboratory according to its function. The student observation sheet contains 17 questions that have passed the midwifery and education expert test, then tested to 77 students with the results of the Alpha Cronbach reliability test of 0.86 > 0.6 which are in the category of